Desenvolvimento de sensores eletroquímicos com utilização de nanotubos de carbono e diferentes mediadores na determinação de Peróxido de Hidrogênio e Epinefrina - Lopes , Cleylton Bezerra (2014)
This paper describes the development of two chemically modified electrodes (CME). The two systems were developed using multi-walled carbon nanotubes (MWCNT). The first system was developed on glassy carbon electrodes (GCE) with MWCNT and film of cobalt oxides (GCE/MWCNT/Co) for determination of hydrogen peroxide (H2O2) and the second system with MWCNT and ferulic acid (FA) (GCE/MWCNT/FA) for determination of epinephrine (EP). The techniques herein employed were cyclic voltammetry, cronoamperometry, which were used to study the electrochemical behavior of modified electrodes, for obtaining kinetic parameters and for the analytical characterization of systems. In addition, hydrodynamic and cronoamperometric studies were carried out with the aim of obtaining information about the H2O2 and EP oxidation process. This device (GCE/MWCNT/Co) was built through the electrodeposition of cobalt oxides on the surface of GCE/MWCNT, and presented a redox pair with E0 = + 0.175 V vs. Ag/AgCl, rate constant of heterogeneous electron transfer (ks) equal to 8.2 s-1 and the analytical figures of merit for H2O2 determination were: linear response range of 3 - 13344 µmol L-1, limit of detection (LOD) of 0.9 µmol L-1, limit of quantification (LOQ) of 3 mol L-1, sensitivity of 4.37 nA L mol-1 and catalytic constant (µobs) of 1,38 x 104 L mol-1 s-1. The system (GCE/MWCNT/FA) was built through the activation of FA on the (GCE/MWCNT), with detection potential for epinephrine of + 0.200 V vs. Ag/AgCl. It presented kobs of 6.99 x 104 L mol-1 s-1, linear response range of 73 - 1406, LOD, LOQ and sensitivity of 22.28 µmol L-1, 73 µmol L-1 and 3.69 nA L µmol-1, respectively.